Determinants of intellectual capital disclosure in initial public offerings: case of Canadian firms - Ghorbel, Hanen; Elleuch, Hela (International Journal of Accounting and Economics Studies, 2016)
The purpose of this paper is to investigate the determinants of intellectual capital informationâ€™s of firms that went through IPO. Â Â Â Â Â Â Â Â Â Â Â Â Â Our sample includes 43 firms that IPOs listed in the Toronto Stock Exchange in 2012 of which the prospectuses for the initial public offering are available. Our study, unlike other studies focuses on the issuing prospectuses. The paper applied a disclosure index comprising of 78 items (Bukh and al (2005)) to quantify the amount of information regarding intellectual capital included in the IPO prospectuses of canadian firms. Multiple regression model and Correlation is used. The results revealed that the managerial ownership, the presence of an audit committee and industry are significantly associated with the voluntary disclosure of information about the intellectual capital in prospectuses. While firm size, age, the audit committeeâ€™ activity and audit quality do not affect disclosure. The results are interpreted in the light of the increasing importance of disclosing information on intellectual capital to the capital market a in case of IPO and constitute a contribution to the ongoing debate on corporate reporting practices.